A multidisciplinary approach to the management of phagophobia. Issue 2 (3rd April 2021) - Begotka, Andrea M.; Silverman, Alan H.; Goday, Praveen
ABSTRACT: Choking phobia, better referred to as phagophobia, leads to significant dietary restriction or complete refusal to eat and drink, which may result in dehydration, and/or malnutrition. Current literature is limited to case reports. Therefore, the current study is a summary of the outcomes from a multidisciplinary approach including medical and behavioral intervention to treat phagophobia. Participants included eight children (4 females) with a mean age of 9.63 years, who consumed nothing to minimal intake orally. A medical workup and appropriate interventions were completed prior to behavioral treatment. Participants completed outpatient behavioral feeding treatment with one requiring intensive outpatient therapy. Three of eight participants started an anti-anxiolytic medication due to significant anxiety. There was a statistically significant increase in food consumption (t = -4.275, p = .004) and weight pre- to post-treatment (t = -4.004, p = .005). The present study is a preliminary investigation supporting the use of a brief multidisciplinary treatment for children with phagophobia so they can resume an age-appropriate diet again. Limitations of this study include a small sample size, convenience sampling, and protocol that is not yet standardized.